Implementação de uma infra-estrutura de monitoramento para avaliação de plataformas MPSOC baseada em NOC - Marczak, Samuel dos Santos (2010)
MPSoCs (Multi-Processor Systems-on-Chip) are complex architectures. As a consequence, verify the system and assure quality of service constraints become complex tasks. Therefore, the research on mechanisms for verifying the system operation is necessary. These mechanisms aim at capturing data about the system status at each moment. This data is captured through the addition of monitors to the architecture. This work presents the implementation of a monitoring infrastructure for NoC-based MPSoCs. The monitoring is captured through traffic monitors added to the NoC (Network-on-Chip). The monitoring infrastructure is integrated to the microkernel of the MPSoC manager processor. Results show that the monitors do not interfere with the NoC global performance and that is possible to obtain the throughput of the flows in the network through the data collected by the monitors. The integration of the monitoring infrastructure to the MPSoC is validated based on matrices added to the microkernel of the manager processor. These matrices store the monitoring values of each NoC router channel.